Innovating assessment and feedback design in teacher education : transforming practice (New York, NY : Routledge, 2024)
"Assessment and feedback are central to the question of how teacher educators can enhance and transform teaching and learning. This edited volume details case studies and empirical research presenting alternative innovative designs for assessment and feedback across a range of programmes, mediums and jurisdictions. While the swift and unexpected digital pivot during the pandemic emphasized how teacher education adopted and facilitated online teaching, supervision and practice, there is now a need for increased attention to support alternative approaches. Innovating Assessment and Feedback Design in Teacher Education considers the perspectives and experiences of teachers, educators and students, while also exploring discipline-specific practices and outcomes, professional competencies as well as issues pertaining to quality, equity, inclusion, accountability, academic integrity and success. Carefully chosen international contributors provide cutting-edge research findings and discuss its practical implications covering the development, deployment and evaluation of classroom-based, hybrid as well as remote approaches. This book elaborates upon the transformative assessment and feedback approaches taken by teacher educators to inform the future landscape of teaching and learning in a digital age. Illustrating key developments in the field, examples of best practice, dialogues integrating the student perspective, worked examples, and international perspectives, this key book is an invaluable resource for teacher educators striving to improve their practice"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Teachers -- Training of; Teachers -- Training of -- Research; Teachers -- In-service training; Teachers -- In-service training -- Research; Educational evaluation; Curriculum-based assessment; Feedback (Psychology).